Analysis of heterogeneous traffic volume studies and optimization of signal cycle length by vissim software - Samuel Peter, C; SiddardhaVarma, V; Sridevi, G (International Journal of Engineering and Technology, 2026)
Now –a-days the design of traffic signal has become an important factor for controlling traffic movement at intersection in towns and cities. Traffic signals not only reduce the accidents but also enable the road safety to users for an effective use of road at intersectionIn the following studies the traffic volume at a particular junction is taken and simulation technique is adopted to reduce the delays, congestion etc. Traffic volume is considered in hourly basis for a week classifying the vehicles into different types and the maximum Peak hour volume is taken and the signal time is designed for the maximum peak hour volume. Signal time can be calculated by Webster’s method in which green time, cycle time can be known, and the obtained results are simulated in VISSIM software which gives a total delay occurring at junction by which signal time at a particular leg may be optimized.
Keywords: Cycle Length; Signal; Webster Method; Peak Hour Volume; VISSIM